A rare case of trichobezoar: Rapunzel's syndrome - Kirkil, Cuneyt; Boyuk, Abdullah; Bulbuller, Nurullah; Aygen, Erhan; Karabulut, Koray (Aves Press Ltd, 2011)
The clinical condition caused by bezoars with long tail named as Rapunzel's syndrome. We present a case with the Rapunzel's syndrome, and also briefly review the relevant literature in this article. We diagnosed a gastric trichobezoar that filling the entire stomach and extending to the forth part of duodenum in a 21 years-old-girl who complained about abdominal pain and weight loss. The bezoar removed by coeliotomy and gastrotomy.
Keywords: Bezoar; Rapunzel's syndrome; trichotillomania